Gen Z’s Work Paradigm Shift: Determinants of Gig Economy Choice in Surakarta - Rahmawati, Fauziyah Nisa; Istiqomah, Nurul - (Signifikan: Jurnal Ilmu Ekonomi, 2025)
Research Originality: The mixed-method approach combines quantitative and qualitative data, thereby providing a more comprehensive view of work preferences among the younger generation. Research Objectives: This research examines Generation Z's work preferences about the gig economy in Surakarta. Research Methods: A mixed method was used, employing Atlas.ti for qualitative analysis and logistic regression for quantitative analysis. Empirical Results: Atlas.ti mapping identified five main categories in the gig economy: type of work, purpose of work, legal guarantees, barriers, and advantages and disadvantages. Logistic regression results revealed that income, reduced work stress, flexible arrangements, and work environment significantly influence Generation Z’s decision to engage in gig work. In contrast, age, gender, and education level showed no significant influence on the choice to work in this sector. Implications: These results highlight the need for legal frameworks that ensure fair protection and social benefits for gig workers, including health insurance, pension schemes, and fair wage standards. JEL Classification: J21, J22, J24, C25 How to Cite:Rahmawati, F. N., & Istiqomah, N. (2025). Gen Z’s Work Paradigm Shift: Determinants of Gig Economy Choice in Surakarta. Signifikan: Jurnal Ilmu Ekonomi, 14(2), 359-372. https://doi.org/10.15408/sjie.v14i2.46135.